the imperial strategies - Grigoryeva, Elena (project baikal, 2018)
The Ministry of Economic Development has recently introduced two documents concerning Russia’s prospects – the Strategy of space development of Russia and the Complex plan of modernization of the transport infrastructure. The principal idea of the documents is to concentrate the inhabitants in a small number of agglomerations with the population of each exceeding three million.The documents immediately evoked a strong and mostly negative response among professional communities. The prospects for Siberia and Far East look especially ominous. In this case, what will the Irkutsk region with the population of 2,404,195 (which is still decreasing) look like? What are the inhabitants of small towns offered to do? Will the proposed strategy turn the majority of Russians into the precariat? Or the whole population of Russia is already the precariat?The geopolitical trends in the country are commented upon by two leading experts, Alexander Kuzmin and Andrey Bokov.